Lecturers' perceptions of teaching observation in Mara University of Technology, Sarawak branch, Samarahan Campus / Sandra Sim Phek Li … [et al.] - Phek Lin Sim, Sandra; Lau Ngee Kiong, Paul; Sim Yian Hua, Linda (2002)
The main goal of education is to provide high quality educational experiences for students. As such, educators have been searching for effective ways to achieve this goal. It is undeniable that "teachers' knowledge about teaching is considered a fundamental component in the improvement of teaching” (Johnson, 1998, p. 23). However, quality teaching requires "not only a teacher who is merely knowledgeable or skilful but is also able to integrate and apply whatever knowledge and skills needed for effective learning to take place” (Schalock, Scahlock and Myton, 1998). In view of this, to ensure quality teaching, MARA University of Technology, Sarawak Branch, Samarahan Campus, (UiTMCSKS) started to officially conduct teaching observations for all the teaching staff since June 1999. The objective of the teaching observation is to promote professional growth and development among staff in the teaching profession.